Designing Multi-Epitope Vaccines to Combat Emerging Coronavirus Disease 2019 (COVID-19) by Employing Immuno-Informatics Approach - Naz, Anam; Shahid, Fatima; Butt, Tariq Tahir; Awan, Faryal Mehwish; Ali, Amjad; Malik, Arif (Frontiers in Immunology, 2020)
A recent pandemic caused by a single stranded RNA virus, COVID-19 initially affecting Chinese population, is now spreading globally. This poses a serious threat which needs to be addressed immediately. Genome analysis of SARS-CoV-2 has revealed its close relation to SARS-coronavirus along with few changes in its spike protein. Spike protein aids in receptor binding and viral entry within the host and therefore represents a potential target for vaccine and therapeutic development. In the current study spike protein of SARS-CoV-2 was explored for potential immunogenic epitopes to design multi-epitope vaccine constructs. S1 and S2 domains of spike proteins were analyzed and two vaccine constructs were prioritized with T cell and B cell epitopes. We adapted a comprehensive predictive framework to provide novel insights into immunogenic epitopes of spike protein which can further be evaluated as potential vaccine candidates against COVID-19. Prioritized epitopes were then modeled using linkers and adjuvants and respective 3D models were constructed to evaluate their physiochemical properties and their possible interactions with ACE2, HLA Superfamily alleles, TLR2 and TLR4.